The Egypt labor market panel survey: Introducing the 2012 round - Ragui Assaad; Caroline Krafft (IZA Journal of Labor & Development, 2013)
This paper introduces the 2012 round of the Egypt Labor Market Panel Survey (ELMPS), a publicly-available nationally representative longitudinal household survey. We describe the key characteristics of the ELMPS, including the samples and questionnaires for each round. Additionally, we examine the attrition processes observed in the panel and discuss the creation of weights to correct for attrition. We compare our data to other statistical sources for Egypt to evaluate the sample's representativeness. To demonstrate how the ELMPS allows for an improved understanding of the labor market, we compare unemployment trends using the ELMPS and other data on unemployment in Egypt.
Keywords: J00; C81; C83; J64; 330; Survey panel data; Public use data; Sample weights; Unemployment; Egypt